Increasing Power Transmission Efficiency of Ultrasonic Transducers Used in Physiotherapy [Fizyoterapide Kullanilan Ultrasonik Dönüştürücülerin Güç İletim Verimliliǧinin Artirilmasi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2018)
The piezoelectric transducers (PZTs), known as ultrasonic transducers, are used for medical treatment and diagnostic purposes. Although PZTs is produced by chemical methods and PZTs need to be modeled due to the electrical properties of chemical materials in order to design the electrical circuits in which PZTs are used. The PZTs used in ultrasonic systems in order to produce acoustic energy need to alternative power. Reactive loads existing in the electrical model of PZT vary depending on frequency that is one of the parameters of alternative power. The electrical impedance matching with the alternative power supply has to be carried out in order to ensure that the produced treatment probes by using PZTs work effectively. Thus, the power applied from the source will be consume on the probe and the effective dose and treatment will be provided. In this study, electrical matching of the probe having a rectangular geometry produced from PZT and operating a central frequency of 1 MHZ which is used in the medical field is presented. The impedance values of the probe and PZTs were measured at the process stages of the probe production and results was given about the results of the matching circuit realized after calculations and simulations. © 2018 IEEE.
Keywords: electrical power transmission; impedance matching; ultrasonic probe